2017
DOI: 10.1038/cddis.2017.321
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MIAT functions as a competing endogenous RNA to upregulate DAPK2 by sponging miR-22-3p in diabetic cardiomyopathy

Abstract: We previously established a rat model of diabetic cardiomyopathy (DCM) and found that the expression of long non-coding RNA myocardial infarction–associated transcript (MIAT) was significantly upregulated. The present study was aimed to determine the pathologic role of MIAT in the development of DCM. MIAT knockdown was found to reduce cardiomyocyte apoptosis and improve left ventricular function in diabetic rats. High glucose could increase MIAT expression and induce apoptosis in cultured neonatal cardiomyocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 18 publications
4
142
0
Order By: Relevance
“…Conversely, lncRNA-MIAT knockdown reduces DAPK2 expression and inhibits apoptosis in cardiomyocytes exposed to high glucose (HG). These results together indicates that lncRNA-MIAT serves as a competing endogenous RNA to upregulate DAPK2 expression by sponging miR-22-3p, as a result, leading to cardiomyocyte apoptosis and subsequent DCM (Xiang et al, 2017). Since the emergence of lncRNAs as regulators of gene expression has shed light on a variety of disease pathogenesis, better understanding of lncRNAs regulatory network will help us uncover the nature of disease further, and ultimately facilitate the improvement of lncRNA-directed diagnostics and therapeutics .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Conversely, lncRNA-MIAT knockdown reduces DAPK2 expression and inhibits apoptosis in cardiomyocytes exposed to high glucose (HG). These results together indicates that lncRNA-MIAT serves as a competing endogenous RNA to upregulate DAPK2 expression by sponging miR-22-3p, as a result, leading to cardiomyocyte apoptosis and subsequent DCM (Xiang et al, 2017). Since the emergence of lncRNAs as regulators of gene expression has shed light on a variety of disease pathogenesis, better understanding of lncRNAs regulatory network will help us uncover the nature of disease further, and ultimately facilitate the improvement of lncRNA-directed diagnostics and therapeutics .…”
Section: Introductionmentioning
confidence: 89%
“…Cells were incubated with 5.5 mM glucose (NG) or 25 mM glucose (HG) for 24 h in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) (Biological Industries, Beit-Haemek, Israel) at 37 • C incubator with 5% CO 2 . Primary cardiomyocytes in HG group were untreated or treated with 100 µM CASP1 inhibitor Ac-YVAD-CMK, according to previous studies (Xiang et al, 2017). Knocking down experiments were performed using X-treme GENE siRNA transfection reagent (Roche, Germany) for small interfering RNA (siRNA) against lncRNA-MIAT (siMIAT), miR-214-3p mimics (miR-214-3p), or anti-miR-214-3p oligonucleotide (AMO-214-3p) with corresponding negative controls (si-NC, NC, AMO-NC), respectively.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…For example, the lncRNA H19 is downregulated in DCM and influences apoptosis via miR-675 and VDAC1 [21]. The lncRNA MIAT is upregulated in high glucose-treated cardiomyocytes and STZ-induced mice, and it sponges miR-22-3p to regulate DAPK2 expression [22]. The lncRNA MALAT1 is upregulated in DCM rats and is associated with the apoptosis of cardiomyocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic cardiomyopathy (DCM) is a disorder of the heart muscle in people with diabetes and carries a substantial risk for the subsequent development of heart failure . The main features of DCM are metabolic disorders, which are often accompanied by oxidative stress, local inflammation, myocardial fibrosis, and cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of nonprotein‐coding RNAs longer than 200 nucleotides . They have critical roles in various biological processes, including gene expression regulation, genomic imprinting, nuclear‐cytoplasmic trafficking, RNA splicing, and translational control . Recent studies indicated that lncRNAs extensively participate in the development of diverse cardiac diseases, such as cardiac ischaemia, hypertrophy, and heart failure .…”
Section: Introductionmentioning
confidence: 99%